Magnetic field-induced non-linear transport in HfTe5. Issue 10 (26th November 2021) - Zhang, Cheng; Yang, Jinshan; Yan, Zhongbo; Yuan, Xiang; Liu, Yanwen; Zhao, Minhao; Suslov, Alexey; Zhang, Jinglei; Pi, Li; Wang, Zhong; Xiu, Faxian
Abstract: The interplay of electron correlations and topological phases gives rise to various exotic phenomena including fractionalization, excitonic instability and axionic excitation. Recently discovered transition-metal pentatellurides can reach the ultra-quantum limit in low magnetic fields and serve as good candidates for achieving such a combination. Here, we report evidence of density wave and metal-insulator transition in HfTe5 induced by intense magnetic fields. Using the non-linear transport technique, we detect a distinct non-linear conduction behavior in the longitudinal resistivity within the a–c plane, corresponding to the formation of a density wave induced by magnetic fields. In high fields, the onset of non-linear conduction in the Hall resistivity indicates an impurity-pinned magnetic freeze-out as the possible origin of the insulating behavior. These frozen electrons can be gradually reactivated into mobile states above a threshold of electric field. This experimental evidence calls for further investigation into the underlying mechanism of the bulk quantum Hall effect and field-induced phase transitions in pentatellurides. Abstract : The nonlinear conduction is induced by magnetic fields in HfTe5, suggesting the formation of the density wave and an impurity-pinned magnetic freeze-out state.